2013
DOI: 10.1177/0308575913477071
|View full text |Cite
|
Sign up to set email alerts
|

Adopting ‘imaginaries’: international adoption in the Spanish press

Abstract: During the last century, mass media joined the institutions which had traditionally provided the elements for shaping perceptions of reality. As a result, they became central to the process of constructing social reality and to the functioning of modern societies. Among these media, the press is especially significant in delineating dominant cultural patterns and social values and through its use of language, building collective 'imaginaries' that influence public opinion. Between 1997 and 2010, 46,638 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…They used a 'pregnancy metaphor', in which waiting for a child was described as a pregnancy lasting for years. Dominant was the 'rescue metaphor': the child would have died, if it had not been adopted (compare Ahluwalia 2007;Anzil 2013;San Román and Rotabi 2017).…”
Section: Methodsmentioning
confidence: 99%
“…They used a 'pregnancy metaphor', in which waiting for a child was described as a pregnancy lasting for years. Dominant was the 'rescue metaphor': the child would have died, if it had not been adopted (compare Ahluwalia 2007;Anzil 2013;San Román and Rotabi 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Drawing from wider literature on child protection, it can be argued that the media contribute significantly to agenda setting, problem framing, resource allocation and public and political opinion and may indirectly shape practice (Ayre, 2001;Franklin and Parton, 1991;Gough, 1996). Anzil (2013) has argued that coverage serves to promote 'collective imaginaries' regarding the nature and operation of adoption, while both Jacobson (2013) and Ali (2014) have found evidence of media influence over perceptions and choices of prospective adopters.…”
Section: Introductionmentioning
confidence: 99%
“…This commentary can be seen to have grown during the 1990s as critique of ‘political correctness’ became more prominent (Franklin, 1998) and by the mid-2000s, Allen (2007: 9) observed that ‘adoption has been well and truly captured by the political and media worlds’. Despite this powerful presence, relevant research has been scant, with notable exceptions the treatment of international and domestic adoption in the US (Jacobson, 2013; Potter, 2013), international adoption in Spain (Anzil, 2013) and portrayal of adopted children in Britain (Maxwell and Cook, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural essentialism-or the idea that people from a certain culture have certain predetermined traits-and its use by adoptive families, especially transnationally adopted families, has been analyzed for its troubling consequences for identity construction among adopted children and the creation, dissemination and maintenance of stereotypes and discrimination (Anzil, 2013;De Graeve and Longman, 2013;De Graeve, 2014;Lind, 2012;Howell, 2003Howell, , 2009Hübinette and Andersson, 2012;San Román and Marre, 2013). Another line of research analyzes the consequences of personal essentialism-the belief that individuals have fixed personalities-on childrearing practices and outcomes (Dix and Grusec, 1985;Dix, and Lochman, 1990;Snyder et al, 2005).…”
Section: Introductionmentioning
confidence: 99%